Grappling with the Legacies of Anthro-Cast: The Work of Bones in the Age of Mechanical Reproduction - Colwell, Chip; Rutherford, Danilyn (Current Anthropology, 2025)
This article critically examines the ethical and historical complexities surrounding the use of replicas of human and mammalian remains in anthropological work. Using the Wenner-Gren Foundation's Anthro-Cast program-which created and distributed fossil ca
Keywords: Contemporary Anthropology; Mechanical Reproduction; Work of Bones; Anthro-Cast